Stent placement in pancreatic disease, when, which and why? – a current perspective - Conrad, Claudio C.; Ellrichmann, Mark (Frontiers in Gastroenterology, 2023)
Introduction Stenting of the pancreas is a challenging task for the interventional gastroenterologist. The indications for pancreatic stent implantation are either prophylactic or therapeutic. We give an overview of currently available literature and techniques for the respective indications of pancreatic stent placement. Methods A structured literature research was conducted (Pubmed.gov) primarily using the following key words: interventional endoscopy, pancreatic stenting, post-ERCP pancreatitis, pancreatic Q8 fistulae, pancreas divisum. Results Prophylactic stent implantation aims to prevent PEP by using thin (3-5 Fr) and short (3-5 cm) designated pancreatic stents at least in high-risk patients. Therapeutic stent placement is intended to restore the proper flow of pancreatic secretion with stenoses, leaks, fistulas or anatomical malformation of the pancreatic duct. Depending on the etiology, plastic stents or SEMSs are used. Another field of pancreatic stenting represents EUS-guided puncture with stent implantation as an alternative access to the main pancreatic duct when transpapillary access is impossible. In addition to the implantation of plastic stents, which achieve good results, LAMS implantation can be discussed as an alternative access route. Discussion The field of pancreatic stenting is complex and belongs in the hands of experienced endoscopists in specialized institutions. This can ensure that the patient receives the optimal treatment with the best possible outcome.